Evaluación de las técnicas de detección del VPH en los programas de cribado para cáncer de cuello uterino Assessment of hpv detection assays for use in cervical cancer screening programs - M Paz Cañadas; Belén Lloveras; Attila Lorincz; Maijo Ejarque; Rebeca Font; F. Xavier Bosch; Silvia de Sanjosé (Instituto Nacional de Salud Pública, 2006)
OBJETIVO: La identificación de la infección por tipos de alto riesgo del virus del papiloma humano (VPH) es una herramienta útil para el cribado de cáncer del cuello uterino. Las distintas técnicas aplicadas para su detección deben contrastarse y validarse para su empleo en la tamización poblacional. MATERIAL Y MÉTODOS: Se evalúan tres técnicas para la detección del VPH en 166 muestras cervicales procedentes de mujeres atendidas en una clínica de dermatología en Oviedo (España): a) PCR-EIA mediante consensos MY09/MY011; b) PCR con line blot hybridization (PCR-LBH) con consensos PGMY; y c) hybrid capture 2. RESULTADOS: El ADN-VPH se reconoció en 29.5%, 25.3% y 24.7%, de acuerdo con el ensayo. La concordancia global entre PCR-EIA, PCR-LBH y HC2 fue de 73.5% con los valores de kappa superiores a 0.56 entre los ensayos (p<0.001). CONCLUSIONES: La prevalencia de tipos de alto riesgo oncogénico así como de las lesiones fue similar en los tres ensayos. En virtud de que las técnicas son comparables, su elección debe basarse en las condiciones individuales de cada laboratorio y el volumen de muestras por procesar. OBJECTIVE: Detection of high-risk human papillomavirus types (HPV) infection is an important tool in the screening of cervical cancer and triage of cytological abnormalities. The different techniques for detection of this cancer need to be contrasted and validated for use in population screening. MATERIAL AND METHODS: Cervical cell samples were collected from 166 women attending a dermatology clinic in Oviedo (Spain). We evaluated the performance of three different assays for VPH detection. The methods utilized were 1) In-house PCR-EIA using L1 consensus primers MY09/MY11, 2) A PCR-reverse line blot hybridization (PCR-LBH) that uses L1 consensus PGMY primers. 3) Hybrid Capture 2. All assays were performed blinded. The kappa statistic was used to test for global agreement between assay pairs. RESULTS: HPV DNA was detected in 24,7%, 25,3% and 29,5% of the women, respective to the assay. The overall agreement between the in-house PCR, PCR-LBH and HC2 was (73.5%) with all kappa values between assay pairs exceeding 0.56 (p<0.001). CONCLUSION: The three HPV assays were equally accurate in estimating high-risk HPV prevalence and HPV-related lesions. The method for HPV detection must be decided depending on the goals of the search (screening, follow-up or molecular studies).